Experimental influence of a splitter vane on the flow fields in a wide-angled diffuser. Issue 1 (June 2021) - Guo, Miao; Meng, Xv; Zuo, Zhigang; Liu, Shuhong
Abstract: Based on PIV and high-speed photography technology, the lengths and area ratios of flow separation zone under different Reynolds numbers Re in a diffuser with a fixed angle (28º), with and without a splitter vane were obtained. The flow field, vorticity and the flow distribution (hydrogen bubble tracing) at the downstream vicinity of the outlet of the diffuser under three representative conditions ( Re = 1000, 6000 and 12000) were given. The experimental results show that with increasing Re, the area proportion of the separation zone decreases, but the length proportion of the separation zone increases, because the thickness of the separation zone along the vertical flow direction is reduced. Due to the existence of vane, the area of the corresponding separation zone is always smaller than that without the vane.